Differences between U23 and older semi-professional soccer players in perfectionism and passion: exploring determinant relationship between variables - Ogallar-Blanco, Adelaida Irene; García-Mármol, Eduardo; Clemente, Filipe Manuel; Badicu, Georgian; Liñán-González, Antonio; González-Fernández, Francisco Tomás (Frontiers in Psychology, 2024)
Aim Abundant studies have pointed out that perfectionism and passion are interrelated and that they both can influence performance in a variety of contexts, including sports, however, research on how these variables interact and might affect performance in team sports, such as soccer, is still scarce. The aim of this study is to analyze differences in perfectionism and passion between under-23 years-old (U23) and older semi-professional soccer players, as well as to study the possible relationship between these two psychological variables. Methods Participants (N = 130 healthy semi-professional Spanish soccer players) were divided into two equivalent groups according to the participants age, U23 (N = 65; 21.58 ± 1.91 years) and older than 24 years (N = 65; 30.03 ± 3.72 years) and completed self-reports on perfectionism and passion. Results Independent samples t-test determined significant differences between the U23 Group and the >24 Group in perfectionism global score and concern over mistakes (maladaptive perfectionism), and in time, value, and passion. Multiple regression analyses revealed that obsessive passion predicted maladaptive subdimensions of perfectionism, while harmonious passion predicted adaptive perfectionism. Discussion U23 soccer players show higher levels of maladaptive perfectionism, time, value, and passion in relation with soccer than older players, probably because at this stage pressure to become professionals and to develop their technical, tactical, and physical skills is higher than in later stages. Conclusion Identifying differences between different age groups can help professionals in tailoring their interventions and strategies to address the specific needs of athletes at different stages of development more effectively, and to optimize mental focus, reduce stress, to promote a healthy mindset for optimal performance in soccer players, furthermore, the study of moderating effects of factors such as team dynamics or coaching styles on these constructs is advised.